Genetic and codon usage bias analyses of polymerase genes of equine influenza virus and its relation to evolution - Bera, Bidhan Ch. (BMC Genomics, 2017)
BACKGROUND: Equine influenza is a major health problem of equines worldwide. The polymerase genes of influenza virus have key roles in virus replication, transcription, transmission between hosts and pathogenesis. Hence, the comprehensive genetic and codon usage bias of polymerase genes of equine influenza virus (EIV) were analyzed to elucidate the genetic and evolutionary relationships in a novel perspective. RESULTS: The group - specific consensus amino acid substitutions were identified in all polymerase genes of EIVs that led to divergence of EIVs into various clades. The consistent amino acid changes were also detected in the Florida clade 2 EIVs circulating in Europe and Asia since 2007. To study the codon usage patterns, a total of 281,324 codons of polymerase genes of EIV H3N8 isolates from 1963 to 2015 were systemically analyzed. The polymerase genes of EIVs exhibit a weak codon usage bias. The ENc-GC3s and Neutrality plots indicated that natural selection is the major influencing factor of codon usage bias, and that the impact of mutation pressure is comparatively minor. The methods for estimating host imposed translation pressure suggested that the polymerase acidic (PA) gene seems to be under less translational pressure compared to polymerase basic 1 (PB1) and polymerase basic 2 (PB2) genes. The multivariate statistical analysis of polymerase genes divided EIVs into four evolutionary diverged clusters - Pre-divergent, Eurasian, Florida sub-lineage 1 and 2. CONCLUSIONS: Various lineage specific amino acid substitutions observed in all polymerase genes of EIVs and especially, clade 2 EIVs underwent major variations which led to the emergence of a phylogenetically distinct group of EIVs originating from Richmond/1/07. The codon usage bias was low in all the polymerase genes of EIVs that was influenced by the multiple factors such as the nucleotide compositions, mutation pressure, aromaticity and hydropathicity. However, natural selection was the major influencing factor in defining the codon usage patterns and evolution of polymerase genes of EIVs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-017-4063-1) contains supplementary material, which is available to authorized users.